2020
DOI: 10.2471/blt.20.261099
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Economic globalization and the COVID-19 pandemic: global spread and inequalities

Abstract: DISCLAIMER This paper was submitted to the Bulletin of the World Health Organization and was posted to the COVID-19 open site, according to the protocol for public health emergencies for international concern as described in Vasee Moorthy et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The most frequent researches are focused on the vulnerability of the population to the epidemic, such as those carried out by Jordan et al [ 12 ], DeCaprio, et al [ 13 ] or Lakhani [ 14 ], the latter framed in Melbourne. There are also studies that analyze the socio-economic impact of the pandemic [ 15 ]. Sajadi et al [ 16 ] and O’Reilly et al [ 17 ], among others, focus on the explanatory factors that can influence the contagion pattern, such as dynamic (e.g., population flows), and environmental elements (especially climate).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent researches are focused on the vulnerability of the population to the epidemic, such as those carried out by Jordan et al [ 12 ], DeCaprio, et al [ 13 ] or Lakhani [ 14 ], the latter framed in Melbourne. There are also studies that analyze the socio-economic impact of the pandemic [ 15 ]. Sajadi et al [ 16 ] and O’Reilly et al [ 17 ], among others, focus on the explanatory factors that can influence the contagion pattern, such as dynamic (e.g., population flows), and environmental elements (especially climate).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that the rapid spread of COVID-19 around the world tended to appear rst in the most economically developed regions where high-level international trade and commercial activities were prevalent. With initially spreading along the routes of international trade between the developed regions, the virus spread later to the developing parts [20]. In our study, the higher coe cient was observed in the midlands and northern cities in comparison with the southern cities of China in the GWPR model.…”
Section: Discussionmentioning
confidence: 43%
“…Waterson, 2021), Western societies have clearly played a role in its propagation and development-in part, through their reluctance to accept that the epidemic could be controlled without access to a vaccine, as seems largely to have happened in South East Asia (An and Tang 2020). As Ludovic et al (2020) have highlighted, integration into a globalized market economy has been one of the drivers of the COVID-19 pandemic. Indeed, countries with higher levels of trade also experienced a higher number of COVID-19 cases in april 2020.…”
Section: Diseases As External Enemies: the Exogenous Dialecticmentioning
confidence: 99%